The Role of Tax Incentives in Attracting Foreign Direct Investment - Prabhakaran , Dr.M.; Sobti, Sakshi; Gupta, Mohit; Gupta , Dr. Ashish; Kumari , Dr. Sweta; Sahoo, Dr. Dhruti Sundar; prabhakaran.m@jainuniversity.ac.in, S. Agila (International Journal of Accounting and Economics Studies, 2025)
The last two decades of the 20th century brought about a significant shift in how many developing countries viewed foreign investment, coinciding with a remarkable global surge in Foreign Direct Investment (FDI). Unlike the past, when these nations were often wary of inward FDI, many now see it as a key driver for their development and actively compete to attract it. By the end of the 20th century, numerous countries had reformed their political and economic systems to draw in more FDI. A lot of nations moved away from socialism in its various forms and adopted market-oriented economies. In several Eastern European countries, mass privatization occurred largely due to foreign investments. The landscape of private foreign investment in developing and less developed countries is extensive, complex, and often controversial, and it has been somewhat overlooked in terms of data collection and analysis compared to other economic development forms. Today, the global economy relies heavily on private and foreign capital. The recent surge in FDI flows has sparked interest in viewing Transnational Corporations (TNCs) as crucial engines of growth for developing nations, especially in India, where FDI is essential for sustained economic growth. Consequently, both developed and developing countries are competing to attract FDI through various strategies, including joint ventures, mergers, and acquisitions. This study aims to explore several issues related to the current FDI inflows and further assess their impact on industrial development in India, focusing on the effects and determinants of FDI within the framework of liberalization, privatization, and globalization (LPG).